2006
DOI: 10.1515/hf.2006.008
|View full text |Cite
|
Sign up to set email alerts
|

Creating water-repellent effects on wood by treatment with silanes

Abstract: Three types of silanes were tested for their ability to impart hydrophobicity to solid wood samples: a tetraalkoxy silane bearing four hydrolysable alkoxy groups; two alkyl-trialkoxy silanes; and two multifunctional oligomeric silane systems. The first two types were applied as monomeric silane solutions and pre-condensed sols. The water uptake of treated wood was considerably reduced, especially after treatment with multifunctional waterborne silane systems, while uptake of gaseous water was not changed. Init… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
83
0
5

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 129 publications
(90 citation statements)
references
References 11 publications
2
83
0
5
Order By: Relevance
“…This suggests that ELO has been attached to the cell walls as a cover layer to block the sorption sites in the cell wall. A similar observation was reported by Donath et al (2006) on silane-modified wood. The results indicated also that the DS of modified samples could be improved by impregnation of a diluted AA in the first step (A5 treatment), which was demonstrated by the relatively high ASE and uniform ASE′.…”
Section: Asesupporting
confidence: 90%
“…This suggests that ELO has been attached to the cell walls as a cover layer to block the sorption sites in the cell wall. A similar observation was reported by Donath et al (2006) on silane-modified wood. The results indicated also that the DS of modified samples could be improved by impregnation of a diluted AA in the first step (A5 treatment), which was demonstrated by the relatively high ASE and uniform ASE′.…”
Section: Asesupporting
confidence: 90%
“…A treatment with siloxanes increased the water repellency of wood (Donath et al 2006(Donath et al , 2007, but did not considerably influence the sorption behaviour of wood. Siloxanes containing amino-functional groups showed protective effectiveness against wood destroying basidiomycetes particularly the brown rot fungi Coniophora puteana and Gloeophyllum trabeum in laboratory durability tests according to EN 113 (Donath 2004).…”
Section: Introductionmentioning
confidence: 84%
“…The reduction in water uptake is caused by blocking the main penetration paths such as pits, ray cells and ray tracheids (Donath et al 2006). However, the moisture content of the surface layer might still be high enough to allow Fig.…”
Section: Weathering Characteristicsmentioning
confidence: 99%
“…Furthermore, once the retention of the biocides in the wood falls below a certain threshold, the retained biocides are no longer able to protect the wood adequately. It has been suggested that water repel-* Corresponding author: liesbeth.devetter@ugent.be lents like oils, waxes and silicones, can be combined with biocides for wood in use class 3 conditions being outdoor usage out of ground contact (Donath et al, 2006a;2006b). The primary purpose of these products is to interfere in the woodmoisture relation to protect the wood, but they are also supposed to prevent leaching of biocides during service life (Donath et al, 2006a;2006b;Mai and Militz, 2004;Taylor and Cooper, 2003;Zahora, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…It has been suggested that water repel-* Corresponding author: liesbeth.devetter@ugent.be lents like oils, waxes and silicones, can be combined with biocides for wood in use class 3 conditions being outdoor usage out of ground contact (Donath et al, 2006a;2006b). The primary purpose of these products is to interfere in the woodmoisture relation to protect the wood, but they are also supposed to prevent leaching of biocides during service life (Donath et al, 2006a;2006b;Mai and Militz, 2004;Taylor and Cooper, 2003;Zahora, 2000). Their suitability, mode of action and location inside wood once applied has been investigated (De Vetter et Article published by EDP Sciences positive results, also conflicting data are reported about the effect of water repellents, e.g.…”
Section: Introductionmentioning
confidence: 99%